Quercetin supplementation alters adipose tissue and hepatic transcriptomes and ameliorates adiposity, dyslipidemia, and glucose intolerance in adult male rats - Kábelová, Adéla; Malínská, Hana; Marková, Irena; Hűttl, Martina; Chylíková, Blanka; Šeda, Ondřej (Frontiers in Nutrition, 2022)
Quercetin, a flavonoid present in many fruits and vegetables, exhibits beneficial effects towards abnormalities related to metabolic syndrome. In this study, to further investigate metabolic and transcriptomic responses to quercetin supplementation, we used a genetic model of metabolic syndrome. Adult male rats of the PD/Cub strain were fed either a high-sucrose diet (HSD; control PD rats) or HSD fortified with quercetin (10 g quercetin/kg diet; PD-Q rats). Morphometric and metabolic parameters, along with transcriptomic profiles of the liver and retroperitoneal fat, were assessed. The relative weights of epididymal and retroperitoneal fat were significantly decreased in quercetin-treated animals. Furthermore, a smaller area under the glycemic curve along with a decreased level of fasting insulin were detected in PD-Q rats. While no changes in total cholesterol levels were observed, the overall level of triglycerides decreased in the serum and the liver of the PD-Q rats. The transcriptomic profile of the liver and the adipose tissue corroborated the metabolic and morphometric findings, revealing the pattern consistent with insulin-sensitizing changes, with major regulator nodes being Pparg, Adipoq, Nos2 and Mir378. In conclusion, quercetin supplementation improves abnormalities related to metabolic syndrome, namely adiposity, dyslipidemia and glucose intolerance.